2023
DOI: 10.1111/jgh.16154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a combination of pemafibrate and a mild low‐carbohydrate diet on obese and non‐obese patients with metabolic‐associated fatty liver disease

Abstract: Background and Aim: Recently, pemafibrate and a low-carbohydrate diet (LCD) have each been reported to improve fatty liver disease. However, it is unclear whether their combination improves fatty liver disease and is equally effective in obese and non-obese patients. Methods: In 38 metabolic-associated fatty liver disease (MAFLD) patients, classified by baseline body mass index (BMI), changes in laboratory values, magnetic resonance elastography (MRE), and magnetic resonance imaging-proton density fat fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This study revealed that pemafibrate significantly increased the ALT normalization rate compared to bezafibrate. Other studies have shown that pemafibrate improves the liver function ( 31 ). Improvement in ALT levels is linked to improvement in hepatic inflammation and steatosis, leading to improvement in liver fibrosis and liver-related complications ( 25 , 32 - 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed that pemafibrate significantly increased the ALT normalization rate compared to bezafibrate. Other studies have shown that pemafibrate improves the liver function ( 31 ). Improvement in ALT levels is linked to improvement in hepatic inflammation and steatosis, leading to improvement in liver fibrosis and liver-related complications ( 25 , 32 - 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…At 3, 6, and 12 months, ALT levels were significantly decreased in both groups (p <0.05). The median (IQR) ALT levels at entry and 3, 6, and 12 months in patients using pemafibrate in the sensitivity analysis of patients with ALT <100 IU/L were 52 (40-64), 29 (25-56), 31 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37), and 26 (20-38) IU/L, respectively. Similarly, in patients with bezafibrate, the median (IQR) ALT levels at entry and 3, 6, and 12 months were 66 (61-69), 43 (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52), 41 , and 39 (32-66) IU/L, respectively.…”
Section: Changes In the Alt Level During Follow-upmentioning
confidence: 99%
“…The first study by Shinozaki et al [ 85 ] treated 71 patients for 6 months, finding that lean patients experienced a greater reduction in ALT and serum mac-2 binding protein glycosylation isomer than obese patients. The second study by Suzuki et al [ 86 ] treated 38 patients for 12 months and found a strong association in the decrease of ALT, AST, hepatic steatosis, and fibrosis in both lean and obese patients. Canagliflozin at a dosage of 100 mg once daily was evaluated in 20 patients with T2DM and NAFLD, but due to only one patient being lean, the results were inconclusive in this population[ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some novel agents for dyslipidemia have been introduced to clinical practice, such as ezetimibe, pemafibrate and others [15,16]. These agents can contribute more for clinical efficacy by combination treatment with statins [17,18].…”
Section: Discussionmentioning
confidence: 99%